Evaluación del impacto de la propuesta pedagógica PRONEPE (Estudio realizado en los Centros de Desarrollo Infantil del Sector Cacha) - Bunay Bravo, Luis Humberto (2000)
Introduction. Framework. Background. Formulation of problem. Delimitation of the investigation. Hypothesis. Justification. Goals. Preschool education alternative. The child and child development. Child Development Centers. Kindergartens and community educators. Features Child Development 4-5 years, and 5-6 years. Social area. Area of language. Cognitive Area. Motor development. Bilingual intercultural non-formal curriculum. The goals of the pedagogical approach PRONEPE. Communication and language skills. The PRONEPE methodologies. Planning the Pedagogical Proposal PRONEPE. Methodological Framework: Population. Sample. System Hypothesis. Conclusions. Recommendations. Annexes. Bibliography.